Circulating lymphocyte levels and relationship with infection status in patients with relapsing–remitting multiple sclerosis treated with daclizumab beta. (November 2018) - Giovannoni, Gavin; Wiendl, Heinz; Turner, Benjamin; Umans, Kimberly; Mokliatchouk, Oksana; Castro-Borrero, Wanda; Greenberg, Steven J; McCroskery, Peter; Giannattasio, Giorgio
Background: Reversible lymphocyte count reductions have occurred following daclizumab beta treatment for relapsing–remitting multiple sclerosis. Objective: To analyse total and differential lymphocyte levels and relationship with infection status. Methods: In DECIDE, blood samples were collected at 12-week intervals from daclizumab beta- ( n = 919) or intramuscular interferon beta-1a–treated ( n = 922) patients. Infections/serious infections were assessed proximate to grade 2/3 lymphopenia or low CD4 + /CD8 + T-cell counts. Total safety population (TSP) data were additionally analysed from the entire clinical development programme ( n = 2236). Results: Over 96 weeks in DECIDE, mean absolute lymphocyte count (ALC), CD4 + and CD8 + T-cell counts decreased <10% (7.1% vs 1.6%, 9.7% vs 2.0%, 9.3% vs 5.9%: daclizumab beta vs interferon beta-1a, respectively); shifts to ALC below lower limit of normal occurred in 13% versus 15%, respectively. Grade 3 lymphopenia was uncommon (TSP: <1%) and transient. Lymphocyte changes generally occurred within 24 weeks after treatment initiation and were reversible within 12 weeks of discontinuation. In DECIDE, mean CD4 + /CD8 + T-cell counts were similar regardless of infection status. TSP data were consistent with DECIDE. Conclusion: When observed, ALC and CD4 + /CD8 + T-cell count decreases in daclizumab beta–treated patients were generally mild-to-modest, reversible upon treatment discontinuation and not associated with increased risk of infections, including opportunistic infections.